Defining Minimal Clinically Important Difference and Patient Acceptable Symptom State After the Latarjet Procedure. Issue 10 (August 2022) - Menendez, Mariano E.; Sudah, Suleiman Y.; Cohn, Matthew R.; Narbona, Pablo; Lädermann, Alexandre; Barth, Johannes; Denard, Patrick J.
Background: The Latarjet procedure is one of the most well-established treatment options for anterior shoulder instability. However, meaningful clinical outcomes after this surgery have not been defined. Purpose: This study aimed to establish the minimal clinically important difference (MCID) and Patient Acceptable Symptom State (PASS) for commonly used outcome measures in patients undergoing the Latarjet procedure and determine correlations between preoperative patient characteristics and achievement of MCID or PASS. Study Design: Case series; Level of evidence, 4. Methods: A multicenter retrospective review at 4 institutions was performed to identify patients undergoing primary open Latarjet procedure with minimum 2-year follow-up. Data collected included patient characteristics (age, sex, sports participation), radiological parameters (glenoid bone loss, off-track Hill-Sachs lesion), and 4 patient-reported outcome measures (collected preoperatively and 2 years postoperatively): the American Shoulder and Elbow Surgeons (ASES) score, the Single Assessment Numeric Evaluation (SANE), the visual analog scale (VAS) for pain, and the Western Ontario Shoulder Instability Index (WOSI). The MCID and PASS for each outcome measure were calculated, and Pearson and Spearman coefficient analyses were used to identify correlations between MCID or PASS and preoperative variables (age, sex, sports participation, glenoid bone loss, off-track Hill-Sachs lesion). Results: A total of 156 patients were included in the study. The MCID values for ASES, SANE, VAS pain, and WOSI were calculated to be 9.6, 12.4, 1.7, and 254.9, respectively. The PASS values for ASES, SANE, VAS pain, and WOSI were 86.0, 82.5, 2.5, and 571.0, respectively. The rates of patients achieving MCID were 61.1% for VAS pain, 71.6% for ASES, 74.1% for SANE, and 84.2% for WOSI. The rates of achieving PASS ranged from 78.4% for WOSI to 84.0% for VAS pain. There was no correlation between any of the studied preoperative variables and the likelihood of achieving MCID or PASS. Conclusion: This study defined MCID and PASS values for 4 commonly used outcome measures in patients undergoing the Latarjet procedure. These findings are essential for incorporating patient perspectives into the clinical effectiveness of the Latarjet procedure and provide valuable parameters for the design and interpretation of future clinical trials.